Experiences of newly diagnosed cancer patients in confronting the finitudes of life: a qualitative systematic review protocol. (December 2018) - Stanic, Jelena; Perrenoud, Béatrice; Rochat, Etienne; Ballabeni, Pierluigi; Jaques, Cécile; Schaer-Chaudhry, Anne-Claude; Zumstein-Shaha, Maya
Abstract : Review question: What is the experience of newly diagnosed patients with cancer when facing the finitude of life and undergoing initial anti-cancer treatment?